The V-ATPase: small cargo, large effects - Schumacher, Karin; Krebs, Melanie (Current opinion in plant biology, 2010)
About 30 years ago seminal reports of anion-sensitive proton-pumping activity associated with microsomal membranes initiated research on the plant vacuolar-type H+-ATPase (V-ATPase, VHA). Since, it has been firmly established that these complex molecular machines are essential for what can be defined as cellular logistics. In a eukaryotic cell, the flow of goods between compartments is achieved either by protein-mediated membrane transport or via vesicular trafficking. Over the past years, it has become increasingly clear that V-ATPases do not only energize secondary active transport but are also important regulators of membrane trafficking.